Experimental Ergonomic Approach in Analysis of Student Mental Workload in Using Learning Management System - Aiza Yudha Pratama; Achmad Zaki Yamani; Syauqie Muhammad Marier; Nurchasanah Nurchasanah; Muhammad Alim Safa'at (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Student interactions with the devices and software used can result in excessive mental workload, which of course also has an impact on decreasing productivity and work functions and indirectly harms student health, as well as student interactions in using the Learning Management System (LMS). Which is expected to continue to be utilized and developed to achieve greater convenience and profit, LMS is expected to continue to be developed and utilized optimally. This study is intended to analyze the mental workload felt by students in the learning process through LMS. An experimental ergonomics approach is used in this study by applying the modified NASA-TLX method. The results of the research experiment show that students feel a high mental workload when using the assignment module, quiz module, and forum module on the LMS, these modules produce a high mental workload due to cognitive difficulty, instruction complexity, and work habits.